2017
DOI: 10.1016/j.prnil.2017.01.006
|View full text |Cite
|
Sign up to set email alerts
|

Atherosclerosis is associated with erectile function and lower urinary tract symptoms, especially nocturia, in middle-aged men

Abstract: BackgroundAtherosclerosis is a systematic disease in which plaque builds up inside the arteries that can lead to serious problems related to quality of life (QOL). Lower urinary tract symptoms (LUTS), erectile dysfunction (ED), and late-onset hypogonadism (LOH) are highly prevalent in aging men and are significantly associated with a reduced QOL. However, few questionnaire-based studies have fully examined the relation between atherosclerosis and several urological symptoms.Materials and methodsThe study compr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 30 publications
(32 reference statements)
1
9
0
Order By: Relevance
“…In the present study, the serum CRP level was particularly associated with the severity of nocturia. Some reports have demonstrated an association between atherosclerosis and nocturia . Considering the relationship between CRP and atherosclerosis, the association between nocturia and the serum CRP level in our present investigation might be explained by atherosclerosis.…”
Section: Discussionsupporting
confidence: 64%
“…In the present study, the serum CRP level was particularly associated with the severity of nocturia. Some reports have demonstrated an association between atherosclerosis and nocturia . Considering the relationship between CRP and atherosclerosis, the association between nocturia and the serum CRP level in our present investigation might be explained by atherosclerosis.…”
Section: Discussionsupporting
confidence: 64%
“…These findings are supported by another study of 303 Japanese men with late-onset hypogonadism, in which nocturia was found to be associated with a higher brachial-ankle PWV on a multivariate linear regression model after adjustment for serum triglycerides, fasting blood sugar, and total testosterone. 37 As PWV is an indicator of arterial stiffness, 33 these results also support a relationship between nocturia and arteriopathy. 37…”
Section: Association Between Arteriopathy and Nocturiamentioning
confidence: 71%
“…In contrast, in the present study, there was no significant difference in the volume of urinary incontinence evaluated by the 1‐h pad test between the atherosclerosis group and the control group (data not shown). Although the 1‐h pad test included the provocation maneuver “washing hands by running water,” which could induce urgency incontinence, the reason why a significant difference between the two groups was not observed was that stress urinary incontinence occurs mainly due to weakened function of the external urethral sphincter after RARP . Therefore, UUI might be masked by a copious amount of stress urinary incontinence during a 1‐h pad test.…”
Section: Discussionmentioning
confidence: 99%